Analysis of bacteria using zero volt paper spray. Issue 8 (9th February 2016) - Wei, Pu; Bag, Soumabha; Pulliam, Christopher J.; Snyder, Dalton T.; Pielak, Rafal M.; Cooks, R. Graham
Abstract : The application of zero volt paper spray to the discrimination between species of bacteria is demonstrated here. Abstract : The application of zero volt paper spray to the discrimination between species of bacteria is demonstrated here. While absolute signal intensities of representative lipids from bacterial membranes were three orders of magnitude lower than for conventional paper spray performed at high potential (kilovolts), the significant reduction in noise offset this disadvantage, resulting in clear separation in principal component analysis space between Gram positive and Gram negative bacteria as well as excellent separation between bacteria species.